Influence of Sessile Oak Log Characteristics on the Efficiency in Veneer Cutting - Adela-Eliza Dumitrascu; Elena-Camelia Musat; Dorin-Ion Dumitrascu; Valentina Doina Ciobanu; Emilia-Adela Salca (BioResources, 2017)
The sessile oak tree represents 10.5% of the forest area in Romania and is the most widespread indigenous oak species. To select the most suitable domain of use for sessile oak wood, certain dimensional and qualitative criteria were taken into consideration. The aim of the present study was to highlight the influence of some log characteristics (wood diameters and quality) on the efficiency in sessile oak veneer cutting. The authors used a group of sessile oak logs purchased from Targoviste in Southeast Romania. The results analysis indicates the influence of sessile oak log diameters on the veneer efficiency comparative with decorative veneer efficiency by estimation of the cumulative density function (CDF). Analyzing the quality of sessile oak logs, it was found that buds and insect holes were the most important defects that appeared. Also, the regression analysis indicates an acceptable level of the present defects and did not have a significant influence to the veneer cutting efficiency, upon the number of obtained veneer sheets and the surface area of special veneer sheets, respectively.